Urban village: creating a livable and conducive environment for community well being at Kuala Kuantan, Kuantan Pahang / Wan Az'zahara Wan Bazli - Wan Bazli, Wan Az'zahara (2017)
Urban Village is a planning approach towards creating a livable environment. The main focus is to provide a livable environment for the community. Urbanization process had occurred widely in our county, this urges the rural spaces to be encroached for new developments to cater for the rise in population and demands. The urban fringe area is explored slowly and resulted to cultural and environmental loss. The outskirts of the city has been under acknowledged and may slowly disappear. This paper focuses towards enhancing the urban village by providing a livable and healthy environment in Kuala Kuantan for community wellbeing. The importance of preserving and conserving these urban village is high, in order to achieve a sustainable living environment for the present and future generations.